Development of HOTS-Based Assessment Instruments for Evaluating Rhythmic Movement in Elementary Schools - Kurniawan, Andi; Triwahyuni, Eges; Emyus, Ahmad Zaki (Indonesian Journal Publisher in cooperation with Indonesian Social Studies Association (APRIPSI), 2025)
This research is motivated by the importance of The importance of HOTS is one of the essential competencies that students must master in facing the challenges of 21st century education, so it is necessary for teachers to develop HOTS-based assessment instruments. The purpose of this study is (1) Describe validity HOTS-based assessment instruments as evaluating rhythmic movement in elementary schools; (2) Describes practicality and (3) Testing the effectiveness. The research used is 4-D model development research. The instruments used were questionnaires and tests. Based on the results of the research conducted, it was found that HOTS-based assessment instruments for evaluating rhythmic movement in elementary schools. The validity of the instrument is supported by expert assessment which shows that the instrument is in accordance with the objectives of the HOTS assessment. In addition, this instrument has been proven effective in improving students' understanding in significantly improving students' cognitive and psychomotor abilities.